Application of a lithium manganate material in selective electrochemical lithium extraction from shale gas wastewater
Patent Information
- Application Number
- CN202610896914.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-22
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-06-22
AI Technical Summary
Existing technologies struggle to selectively extract lithium from shale gas wastewater efficiently and with low energy consumption, and lithium manganese oxide materials suffer from manganese leaching and structural collapse issues during electrochemical processes.
A spinel-type lithium manganese oxide material (LMO-Al-F) co-doped with aluminum and fluorine was prepared by solid-state sintering and used in a rocking-chair capacitor deionization (RCDI) system to achieve selective insertion and release of lithium ions, strengthen the spinel structure and improve the stability of the material.
It improves lithium adsorption capacity and selectivity, reduces energy consumption, enhances the material's cycle stability and lithium/sodium and lithium/magnesium selectivity factors, adapts to high salinity and complex ionic matrices, and reduces reagent dosage and secondary pollution.
Smart Images

Figure CN122403586B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of wastewater treatment technology, and in particular to the application of a lithium manganese oxide material in the selective electrochemical lithium extraction from shale gas wastewater. Background Technology
[0002] Lithium, due to its excellent energy density, has become the preferred medium for various energy storage devices. Currently, almost all commercially available lithium comes from non-renewable, unevenly distributed lithium mines or lithium-rich brines. The extraction and refining of these resources are energy-intensive and require large amounts of reagents, posing environmental risks.
[0003] The lithium content in shale gas wastewater can meet about 20% of global demand, and low-cost recovery can be achieved using existing infrastructure. However, the lithium concentration in shale gas wastewater is much lower than that in lithium-rich brines, while the concentration of coexisting ions such as sodium and magnesium is hundreds of times higher, making traditional lithium extraction processes such as evaporation, precipitation, and solvent extraction difficult to apply.
[0004] Electroadsorption (including capacitive deionization (CDI) based on lithium-ion sieves) can separate target ions quickly, with low energy consumption and high selectivity. It can be driven by clean energy, requires little reagent, and produces almost no secondary pollution, making it an ideal method for lithium extraction from shale gas wastewater. This separation performance mainly depends on the lithium-ion sieve electrode material—which has appropriately sized vacancies or channels that can selectively separate lithium ions from sodium, magnesium, and other ions based on properties such as ionic radius, hydration radius, charge, and enthalpy of hydration.
[0005] Spinel-type lithium manganese oxide (LMO) is a typical lithium-ion sieve, possessing a three-dimensional tunnel structure that enables selective and rapid lithium transport. It is also low-cost, highly selective, and environmentally friendly. However, the unique electronic configuration of manganese can induce the Jameer-Taylor effect (2Mn). 3+ →Mn 4+ +Mn 2+ This leads to manganese leaching, lattice collapse, and a decrease in electrode adsorption performance and lifespan.
[0006] Ion doping is a key method to improve the adsorption performance and stability of LMO. Metal cations such as magnesium, cobalt, aluminum, iron, and titanium can partially replace Mn. 3+ Stronger MO bonds are formed, improving electrochemical performance, but this may reduce capacity, requiring precise control of the doping amount. Besides cation doping, anion doping such as fluorine and sulfur can replace oxygen at the 32e position in the crystal lattice, enhancing bond energy, stabilizing the structure, and improving adsorption performance by regulating the charge density of the doping sites. Co-doping of cations and anions can simultaneously improve material stability and adsorption capacity, enhancing lithium extraction efficiency.
[0007] The configuration of the capacitive deionization device has a significant impact on the lithium extraction efficiency. Membrane capacitive deionization (MCDI) and hybrid capacitive deionization (HCDI) have strong adsorption capacity, but they have limitations: silver electrodes are efficient but expensive, carbon electrodes are low-cost but have weak chloride ion adsorption and are prone to oxidation and instability, and both types of systems require time-consuming intermittent electrode regeneration.
[0008] In 2016, Smith et al. proposed a rocking chair capacitive deionization (RCDI) system that features continuous adsorption, high capacity, and excellent energy efficiency. This configuration uses an ion exchange membrane to separate two chambers, enabling simultaneous adsorption and desorption, fully utilizing the material's adsorption performance, and resulting in lower operating voltage and energy consumption for the same current. Summary of the Invention
[0009] To address the above technical problems, this invention provides an application of lithium manganese oxide materials in selective electrochemical lithium extraction from shale gas wastewater. This invention successfully prepared aluminum-fluorine co-doped LMO (LMO-Al-F) particles via solid-state sintering and used them as RCDI electrodes for lithium recovery from water. The selectivity of LMO and a series of modified materials for lithium relative to sodium and magnesium was systematically studied, and the mechanism by which aluminum-fluorine doping enhances the lithium selectivity of LMO was revealed through electrochemical analysis.
[0010] The purpose of this invention is to provide an application of lithium manganese oxide material in highly selective electrochemical lithium extraction from shale gas wastewater. The lithium manganese oxide material is a spinel-type lithium manganese oxide co-modified with aluminum and fluorine. In this process, aluminum replaces some manganese sites to increase the average valence state of manganese and strengthen the bulk spinel structure, while fluorine replaces some oxygen sites or accumulates on the material surface to form a fluorine-containing passivation layer. The lithium manganese oxide material serves as the active material of a lithium-ion sieve electrode (i.e., an aluminum-fluorine co-doped lithium manganese oxide electrode), enabling selective insertion and release of lithium ions in the electrochemical lithium extraction system.
[0011] In some embodiments of the present invention, the lithium manganese oxide material is prepared by the following method: Lithium, manganese and aluminum sources are mixed in a solvent, the solvent is heated to evaporate, and the mixture is dried to obtain precursor powder. The obtained precursor powder was calcined in air for the first time to obtain aluminum-doped lithium manganese oxide. The obtained aluminum-doped lithium manganese oxide was mixed and ground with a fluorine source, and then subjected to a second heating and calcination to obtain aluminum-fluorine co-doped lithium manganese oxide.
[0012] In some embodiments of the present invention, the molar ratio of Li, Mn and Al in the lithium source, manganese source and aluminum source is 1:(1.90-1.99):(0.01-0.10), preferably 1:1.95:0.05; The lithium source is selected from one or more of lithium hydroxide (LiOH), lithium carbonate (Li2CO3), lithium acetate (CH3COOLi), and lithium nitrate (LiNO3), with lithium hydroxide (LiOH) being preferred. The manganese source is selected from one or more of manganese acetate (CH3COO)2Mn, manganese nitrate Mn(NO3)2, manganese carbonate MnCO3 and manganese oxide MnO, preferably manganese acetate (CH3COO)2Mn; The aluminum source is selected from one or more of basic aluminum acetate Al(OH)(CH3COO)2·2H2O, aluminum nitrate Al(NO3)3, aluminum acetate (CH3COO)3Al and aluminum hydroxide Al(OH)3, preferably basic aluminum acetate Al(OH)(CH3COO)2·2H2O.
[0013] In some embodiments of the present invention, the first heating and calcination includes two steps: preheating and calcination. The preheating temperature is 400-600°C and the time is 5-9 hours; the calcination temperature is 700-800°C and the time is 8-12 hours; preferably, the preheating temperature is 500°C for 7 hours and the calcination temperature is 750°C for 10 hours.
[0014] In some embodiments of the present invention, the fluorine source is selected from one or more of ammonium fluoride NH4F, lithium fluoride LiF, ammonium hydrogen fluoride NH4HF2 and sodium fluoride NaF, with ammonium fluoride NH4F being preferred.
[0015] In some embodiments of the present invention, the temperature of the second heating and calcination is 350-450°C and the time is 1-4 hours, preferably 400°C and 2 hours.
[0016] The mass ratio of lithium manganese oxide to fluorine source is (50-100):1, preferably about 69:1.
[0017] In some embodiments of the present invention, the preparation of the active material of the lithium-ion sieve electrode includes the following steps: mixing an aluminum-fluorine co-doped lithium manganese oxide material with a binder and a conductive agent, and dispersing it in an organic solvent to form an electrode slurry; coating the electrode slurry on graphite paper and drying it to obtain an aluminum-fluorine co-doped lithium manganese oxide electrode.
[0018] In some embodiments of the present invention, the binder is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, Nafion and sodium carboxymethyl cellulose, preferably polyvinylidene fluoride; The conductive agent is selected from one or more of conductive carbon black, acetylene black, carbon nanotubes, graphene and graphite powder, with conductive carbon black being preferred; The organic solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide and γ-butyrolactone, preferably N-methylpyrrolidone; The mass ratio of the aluminum-fluorine co-doped lithium manganese oxide material, binder, and conductive agent is (70-90):(5-20):(5-20), preferably 8:1:1; The graphite paper measures 4.5cm × 4.5cm × 0.02cm, with an effective working area of 4cm × 4cm and an active material loading of approximately 2.5mg / cm³. 2 .
[0019] In some embodiments of the present invention, the lithium-ion sieve electrode is pre-delithiated at 0.8V (vs. Ag / AgCl) before lithium adsorption to form lithium adsorption vacancies; In some embodiments of the present invention, the shale gas wastewater contains Li + Na + Mg 2+ K + and Ca 2+ One or more coexisting ions; Electrochemical lithium extraction employs a rocking-chair capacitor deionization system, including a lithium manganese oxide electrode, two flow channels, and an anion exchange membrane disposed between the two flow channels. In the rocking chair capacitive deionization system, the flow rate of shale gas wastewater or simulated shale gas wastewater is 3-15 mL / min, preferably 7 mL / min, and it operates in constant flow mode. The applied current density during adsorption is 0.25-0.75 A / m. 2 The preferred value is 0.625 A / m 2 During the desorption process, the same current density is applied in opposite directions.
[0020] The aluminum-fluorine co-doped lithium manganese oxide material for Li + Relative to Na + and Mg 2+ It has selective intercalation capability; when the aluminum-fluorine co-doped lithium manganese oxide material is used for lithium recovery in a ternary mixed solution of LiCl, NaCl and MgCl2 in a molar ratio of 1:100:1, the lithium adsorption capacity is higher than that of undoped lithium manganese oxide, and the lithium / sodium and lithium / magnesium selectivity factors are higher than those of undoped lithium manganese oxide.
[0021] Selective and efficient extraction of lithium from unconventional water sources such as shale gas wastewater is an effective strategy for addressing energy and environmental challenges. Lithium manganese oxide (LMO) is considered an ideal material for lithium electroadsorption recovery due to its high specific capacity, fast lithium-ion transport, low cost, strong lithium selectivity, and environmental friendliness. However, to improve the practicality of LMO, further improvements in its cycle stability and lithium selectivity are still needed. This invention employs an aluminum-fluorine co-doping strategy to modify LMO, enhancing its spinel structure while simultaneously increasing its lithium adsorption capacity.
[0022] Characterization analysis shows that aluminum-fluorine co-modified LMO (LMO-Al-F) has a smaller lattice constant and better electrochemical performance, which is beneficial for efficient and selective adsorption of lithium.
[0023] Experimental results of lithium extraction from simulated shale gas wastewater using a rocking chair capacitive deionization (RCDI) system show that, compared with pure LMO, LMO-Al-F material exhibits higher adsorption capacity (from 4.15 mg / g to 9.54 mg / g), stronger lithium selectivity (lithium / sodium selectivity increased from 756 to 2216, lithium / magnesium selectivity increased from 451 to 1509), and lower energy consumption (from 12.62 Wh / mol Li to 4.21 Wh / mol Li). Furthermore, LMO-Al-F demonstrates superior cycling stability, with a capacity retention of ≥90% after 100 cycles and extremely low manganese leaching. These results indicate that LMO-Al-F material has significant application potential in lithium extraction from shale gas wastewater.
[0024] The technical solution of the present invention has the following advantages over the prior art: This invention demonstrates that aluminum-fluorine co-doped spinel lithium manganese oxide establishes a new performance-stability benchmark for lithium-ion sieve electrodes, enabling practical lithium extraction via RCDI. The co-doped spinel maintains high lithium / magnesium selectivity in various brines and can still rapidly and selectively capture lithium in real shale gas production water, exhibiting strong tolerance to high salinity and complex ionic matrices.
[0025] Mechanistic studies reveal that partial substitution of aluminum ions increases the average valence state of manganese and suppresses Jamie-Taylor distortion; fluorine doping forms a fluorine-rich aluminum surface passivation layer, reducing manganese dissolution. These two factors synergistically lower the lithium migration barrier, protect the spinel structure, and maintain long-term capacity retention.
[0026] Integrating co-doped lithium-ion sieves into an RCDI platform enables continuous operation and rapid electrochemical regeneration, offering superior energy efficiency compared to traditional capacitive deionization and stable performance under high-salt conditions. This low-reagent process is adaptable to renewable electricity, minimizing secondary waste and reducing the carbon and water footprint of lithium recovery. Abundant dopant elements and scalable synthesis processes further highlight the sustainability of this method, demonstrating its potential for widespread application in brine treatment and resource recovery. This lattice engineering strategy can be widely applied to the selective extraction of other key ions. Attached Figure Description
[0027] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein... Figure 1This invention relates to the preparation and physicochemical properties of the materials. (a) Schematic diagram of solid-phase synthesis and surface fluorination preparation of LMO, LMO-Al, LMO-F, and LMO-Al-F. (b, c) SEM images of LMO and LMO-Al-F. (d) HAADF elemental distribution diagrams of Mn, O, Al, and F in LMO-Al-F. (e) XRD patterns (inset: magnified (111) crystal plane diffraction peaks). (f) Lattice constant and cell volume obtained based on XRD refinement. (g, h) High-resolution XPS spectra of Mn2p. (i) Ar + XPS spectra of LMO-Al-F after etching, F1s depth profile.
[0028] Figure 2 This invention relates to the electrochemical performance and kinetic analysis and electrochemical characterization of the original and doped LMO electrodes. The electrochemical characterization includes: (a) cyclic voltammetry (CV) curves; (b) galvanostatic charge-discharge (GCD) curves; (c) electrochemical impedance spectroscopy (EIS) curves; (d) CV curves of LMO-Al-F in different electrolytes; (e) CV curves of LMO-Al-F at different scan rates; and (f) the capacitance control and diffusion control contributions of LMO-Al-F at different scan rates.
[0029] Figure 3 This invention describes the electrochemical lithium extraction performance of LMO and modified LMO. (a) is a schematic diagram of the RCDI battery working principle; (b) shows the applied current and the Li-C channels A and B during cycling. + Concentration changes; (c) Li / Na and Li / Mg separation factors in ternary mixed electrolyte; (d) Lithium adsorption capacity and energy consumption of different electrodes; (e) Ion removal performance in actual shale gas produced water.
[0030] Figure 4 The stability of LMO-Al-F obtained in Example 1 of this invention is similar to that of Li. + The selective enhancement mechanism was studied, and in-situ Raman contour maps were collected during the electrochemical lithiation / delithiation process.
[0031] Figure 5 These are the FTIR spectra of LMO, LMO-F, LMO-Al, and LMO-Al-F obtained in this invention.
[0032] Figure 6 These are the XPS spectra of LMO, LMO-F, LMO-Al, and LMO-Al-F obtained in this invention.
[0033] Figure 7 These are the constant current charge-discharge curves of LMO-Al-F materials under different Al doping levels according to the present invention.
[0034] Figure 8 These are the constant current charge-discharge curves of LMO-Al-F materials under different F doping levels according to the present invention.
[0035] Figure 9 The Li in the LMO electrode and LMO-Al-F electrode obtained in this invention + Diffusion coefficient. (a,b) shows the CV curve of the LMO-Al-F electrode and the corresponding linear fit of peak current with v1 / 2. (c,d) shows the CV curve of the LMO electrode and the corresponding linear fit of peak current with v1 / 2.
[0036] Figure 10 These are the Li / Na and Li / Mg separation factors of LMO-based adsorbents with different F and Al doping ratios according to the present invention; wherein, (a) represents different F doping ratios; and (b) represents different Al doping ratios.
[0037] Figure 11 The present invention describes the Li adsorption capacity (LAC) and energy consumption (EC) of LMO-based adsorbents under different F and Al doping ratios, where (a, c) represent cases with different F doping ratios and (b, d) represent cases with different Al doping ratios.
[0038] Figure 12 This invention relates to the effect of current density on the EC(a), LAC(b), Li / Na and Li / Mg separation factors(c) of LMO-Al-F obtained in Example 1.
[0039] Figure 13 This refers to the cyclic stability of LMO and LMO-Al-F obtained in this invention.
[0040] Figure 14 This is a comparison of XRD patterns before and after cyclic testing of the LMO-Al-F electrode obtained in Example 1 of this invention. Detailed Implementation
[0041] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.
[0042] The data calculation method involved in this invention 1. The lithium adsorption capacity LAC is calculated according to formula (1): LAC=(C0-C t V / m, Equation (1); Where C0 is the initial Li + Concentration, C t Li after electroadsorption + Concentration, V is the volume of the feed solution, and m is the mass of the electrode active material.
[0043] 2. Li + The selectivity factor SF relative to the coexisting ion M (M is Na or Mg) is calculated according to equation (2): SF = (Li / M)recovered liquid / (Li / M)initial liquid, Equation (2); Wherein, (Li / M) recovered solution is the molar ratio of Li to M in the recovered solution, and (Li / M) initial solution is the molar ratio of Li to M in the initial solution.
[0044] 3. Energy consumption EC is calculated according to formula (3): EC=∫I·U·d t / n Li Equation (3); Where I is the applied current, U is the battery voltage, and n Li This refers to the amount of lithium recovered or removed during the unit operation.
[0045] 4. The lithium-ion diffusion coefficient can be calculated based on the linear relationship between the CV peak current and the square root of the scan rate at different scan rates, combined with the Randles-Sevcik equation.
[0046] Method for preparing the electrode of this invention: Aluminum-fluorine co-doped lithium manganese oxide material is mixed with polyvinylidene fluoride and conductive carbon black in a mass ratio of 70-90:5-20:5-20 and dispersed in N-methylpyrrolidone to form an electrode slurry. The electrode slurry is coated on graphite paper and dried to form an aluminum-fluorine co-doped lithium manganese oxide electrode.
[0047] Further, the aluminum-fluorine co-doped lithium manganese oxide material, binder and conductive agent are mixed in a mass ratio of 8:1:1; an organic solvent is added to the resulting mixture and the mixture is ground or stirred to disperse it, forming a uniform electrode slurry, wherein the solid content of the electrode slurry is 60wt%.
[0048] The electrode slurry is uniformly coated onto the surface of the current collector, which is preferably graphite paper. The wet film thickness during coating is 100-500 μm, preferably 200-300 μm. After coating, it is dried at 60-100℃ for 6-12 hours, preferably under vacuum at 80℃, to obtain an aluminum-fluorine co-doped lithium manganese oxide electrode.
[0049] The graphite paper measures 4.5cm × 4.5cm × 0.02cm, with an effective working area of 4cm × 4cm. The resulting electrode has an active material loading of 1.0-5.0 mg / cm³. 2 The preferred concentration is approximately 2.5 mg / cm³. 2 .
[0050] Example 1 This embodiment provides a highly selective electrochemical lithium extraction method from actual shale gas wastewater using aluminum-fluorine co-doped lithium manganese oxide (LMO-Al-F), as detailed below: I. Preparation of LMO-Al-F material: LiOH, manganese acetate ((CH3COO)2Mn), and basic aluminum acetate (Al(OH)(C2H3O2)2) were weighed and added to an appropriate amount of ethanol at a molar ratio of 1:1.95:0.05. 20 mL of ethanol was added for every 1 g of solid raw material to ensure thorough dispersion, resulting in a mixture. The mixture was continuously stirred at 60°C until the ethanol was completely evaporated, yielding a precursor powder. The precursor powder was dried at 110°C, then preheated in air at 500°C for 7 hours, and then calcined at 750°C for 10 hours to obtain an aluminum-doped lithium manganese oxide intermediate. The obtained aluminum-doped lithium manganese oxide intermediate was thoroughly mixed and ground with ammonium fluoride at a mass ratio of 69:1, and then calcined at 400°C for 2 hours to obtain the aluminum-fluorine co-doped lithium manganese oxide material, denoted as LMO-Al-F.
[0051] II. Preparation of LMO-Al-F Electrode: LMO-Al-F active material, polyvinylidene fluoride (PVDF), and conductive carbon black were mixed and ground at a mass ratio of 8:1:1. 3 ml of N-methylpyrrolidone (NMP) was added to disperse the mixture and form a uniform electrode slurry with a solid content of 60 wt%. The resulting electrode slurry was uniformly coated onto graphite paper with dimensions of 4.5 cm × 4.5 cm × 0.02 cm, resulting in an effective working area of 4 cm × 4 cm. After coating, the electrode was dried in an 80°C vacuum oven. The active material loading of the electrode after drying was approximately 2.5 mg / cm³. 2 .
[0052] III. Electrode Pretreatment: Before lithium adsorption, the LMO-Al-F electrode is pre-delithiated at a potential of 0.8V (vs. Ag / AgCl) to create vacancies in the lithium manganese oxide structure for subsequent lithium ion insertion.
[0053] Example 2 This embodiment provides an aluminum-fluorine co-doped lithium manganese oxide (LMO-Al-F) material with different Al source addition amounts for high-selectivity electrochemical lithium extraction from actual shale gas wastewater.
[0054] The preparation method of this embodiment is the same as that of Example 1, except that: the molar ratio of Li, Mn, and Al in Example 1 is 1:1.95:0.05 as a baseline, and the amount of basic aluminum acetate added is adjusted so that the amount of Al source added is 0.5 times, 1 times, and 1.5 times that of Example 1, respectively; correspondingly, the molar ratios of Li, Mn, and Al in the lithium source, manganese source, and aluminum source are 1:1.975:0.025, 1:1.95:0.05, and 1:1.925:0.075, respectively, and the resulting materials are denoted as LMO-0.5Al-F, LMO-Al-F, and LMO-1.5Al-F, respectively.
[0055] LMO-Al-F is the aluminum-fluorine co-doped lithium manganese oxide material obtained in Example 1. The remaining preparation steps, electrode preparation methods, and electrochemical testing conditions are the same as in Example 1.
[0056] Example 3 This embodiment provides an aluminum-fluorine co-doped lithium manganese oxide (LMO-Al-F) material with different amounts of F source addition for high-selectivity electrochemical lithium extraction from actual shale gas wastewater.
[0057] The preparation method of this embodiment is the same as that of Example 1, except that: the amount of ammonium fluoride added is adjusted based on the mass ratio of aluminum-doped lithium manganese oxide intermediate product and ammonium fluoride in Example 1 of 69:1. The amount of ammonium fluoride added is 0.5 times, 1 times and 1.5 times that of Example 1, respectively. Correspondingly, the mass ratio of aluminum-doped lithium manganese oxide intermediate product to ammonium fluoride is about 138:1, 69:1 and about 46:1, respectively. The resulting materials are denoted as LMO-Al-0.5F, LMO-Al-F and LMO-Al-1.5F, respectively.
[0058] LMO-Al-F is the aluminum-fluorine co-doped lithium manganese oxide material obtained in Example 1. The remaining preparation steps, electrode preparation methods, and electrochemical testing conditions are the same as in Example 1.
[0059] Comparative Example 1 This comparative example provides a highly selective electrochemical lithium extraction method from actual shale gas wastewater using aluminum-doped lithium manganese oxide (LMO-Al), as detailed below: The preparation method of this comparative example is basically the same as that of Example 1, except that after obtaining the aluminum-doped lithium manganese oxide intermediate, it is no longer mixed and ground with ammonium fluoride, nor is the 400°C fluorination calcination step performed. The resulting material is denoted as LMO-Al.
[0060] Comparative Example 2 This comparative example provides a highly selective electrochemical lithium extraction process from actual shale gas wastewater using fluorine-doped lithium manganese oxide (LMO-F), as detailed below: The preparation method of this comparative example is basically the same as that of Example 1, except that: basic aluminum acetate is not added in the precursor preparation stage. Undoped lithium manganese oxide is first prepared by drying LiOH and manganese acetate at 110°C, preheating at 500°C for 7 hours, and calcining at 750°C in air atmosphere for 10 hours; then the obtained lithium manganese oxide is mixed and ground with ammonium fluoride and calcined at 400°C for 2 hours. The resulting material is denoted as LMO-F. The corresponding electrode is prepared according to the method described in Example 1.
[0061] Comparative Example 3 This comparative example provides a highly selective electrochemical lithium extraction method from actual shale gas wastewater using lithium manganese oxide (LMO), as detailed below: Similar to the preparation method in Example 1, the difference lies in that: the preparation method of this comparative example is basically the same as that of Example 1, except that: basic aluminum acetate is not added during the precursor powder preparation stage, and no ammonium fluoride surface fluorination treatment is performed after calcination to obtain lithium manganese oxide; the resulting material is denoted as LMO. The corresponding electrode is prepared according to the method described in Example 1.
[0062] Structural characterization The LMO-based electrodes obtained in Example 1 and Comparative Examples 1-3 were structurally characterized, and the results are shown in the figure. Figure 1 , Figure 1 The results show that all samples exhibit characteristic spinel LMO diffraction peaks (JCPDS35-0782), indicating that aluminum / fluorine doping did not alter the overall spinel framework. Notably, the (111) and (400) diffraction peaks of LMO-Al-F are slightly shifted to a higher 2θ angle, suggesting that aluminum-fluorine co-doping induces lattice shrinkage. Refined lattice constants and cell volumes further confirm the lattice shrinkage after co-doping.
[0063] Figure 1 As shown in Table 1, compared with pure LMO, LMO-Al-F particles have smaller size and larger specific surface area, which can enhance the electrode-electrolyte interaction and facilitate lithium-ion intercalation.
[0064] Table 1. BET specific surface area of LMO and Al or F modified LMO
[0065] Figures b and c show high-resolution transmission electron microscopy (HRTEM) and selected area electron diffraction (SAED) images of LMO and LMO-Al-F, revealing clear (111) crystal plane lattice fringes and high crystallinity. The interplanar spacing of LMO-Al-F (4.82 Å) is smaller than that of pure LMO (4.91 Å), directly confirming the lattice shrinkage inferred by XRD at the microscopic level. Elemental plane distribution (e.g.) Figure 1 As shown in Figure d, manganese, oxygen, aluminum, and fluorine are evenly distributed, confirming the successful introduction of the two doping elements.
[0066] Fourier transform infrared spectroscopy (FTIR) Figure 5 The results show that aluminum-fluorine doping makes spinel more porous at 617 cm⁻¹. -1 With 517cm -1 The two nearby characteristic peaks exhibit a blue shift, indicating the formation of stronger Al-O bonds, proving that the introduction of aluminum fluorine makes the structure more stable. These factors collectively lead to a decrease in the lattice constant and lattice contraction.
[0067] X-ray photoelectron spectroscopy (XPS) is used to analyze the chemical properties and surface composition of materials. Figure 6 The results show that, in addition to the characteristic peaks of manganese, oxygen, lithium, and carbon, the aluminum / fluorine-doped samples exhibit unique aluminum and fluorine peaks. High-resolution Mn2p spectra (…) Figure 1 (gh) shows that aluminum doping enhances Mn 4+ / Mn 3+ Fluorine doping lowers this ratio, with the LMO-Al-F ratio falling between the two. Fluorine substitution lowers the average valence state of manganese and increases the valence state of Mn. 3+ To maintain charge balance, after fluorine replaces some oxygen at the 32e position, the total negative charge of the lattice decreases. To maintain electroneutrality, the average valence state of manganese needs to decrease. 4+ The proportion has decreased.
[0068] Aluminum ion radius and Mn 3+ Similar and more likely to replace 16d-bit Mn 3+ It forms a solid solution, reducing Mn 3+ Content. In this invention, aluminum-fluorine co-doping uses surface fluorine doping rather than bulk doping; therefore, fluorine doping does not induce a significant increase in Mn content. 3+ The change only causes the surface portion of Mn 4+ Transform into Mn 3+ And form Mn-F complexes. Argon ion etching enhanced XPS results ( Figure 1 (i) Confirms that as the etching depth increases, the intensity of the fluorine peak continuously decreases, while the aluminum peak remains essentially unchanged. Fluorine forms a fluoride layer on the material surface, providing structural reinforcement; aluminum, on the other hand, effectively strengthens the interior of the crystal lattice. Together, they enable the material to possess both higher capacity and better cycling stability.
[0069] Electrochemical performance testing The original and doped LMO electrodes obtained in the examples and comparative examples were subjected to electrochemical performance and kinetic tests, as follows: A three-electrode system was used, comprising an LMO or modified LMO working electrode, an Ag / AgCl reference electrode, and a platinum sheet counter electrode. The electrolyte was a 1M LiCl, 1M NaCl, or 1M MgCl2 single-salt solution. Cyclic voltammetry was performed with a potential window of 0.4–1.1 V and a scan rate of 1 mV / s. Electrochemical impedance spectroscopy was performed with a 10 mV perturbation near the open-circuit potential, in a frequency range of 1000 kHz to 10 mHz. Constant current charge-discharge was used to evaluate electrode capacity and reversible intercalation / deintercalation responses in different ionic systems. Experimental results are shown below. Figure 2 and Figure 7 .
[0070] Figure 2 As shown in Figure a: In the cyclic voltammetry (CV) curves of LMO and its series of modified samples, all electrode materials exhibit two pairs of redox peaks, corresponding to spinel Li x Lithium in Mn2O4 (x<1) undergoes a two-step reversible insertion / extraction process. The CV curve of LMO-Al-F shows the largest enclosing area and the best specific capacitance.
[0071] Constant current charge-discharge (GCD) test Figure 2 b, Figure 7 The results show that LMO-Al-F has the highest specific capacity, consistent with the CV results, indicating that the doping ratio of this material is optimal. Excess aluminum leads to excessive lattice contraction, local strain imbalance, structural changes, and decreased stability; simultaneously, Mn... 3+ Too low a content will reduce electrochemical activity and weaken lithium intercalation ability, as evidenced by the suppressed redox response in the CV curve of excessive doping.
[0072] Constant current charge-discharge curves show that the discharge capacity decreases and the plateau shortens under suboptimal doping ratios, confirming that excessive doping is detrimental to lithium storage. Excess aluminum also forms a remodeled surface layer that hinders lithium transport, while excessive fluorine leads to Mn... 3+ The significant increase in lithium content and the exacerbation of the Jiang-Taylor effect lead to the formation of new structures that are unfavorable for lithium intercalation, as evidenced by the presence of a heterogeneous peak in XRD at 2θ=37.1°.
[0073] Electrochemical impedance spectroscopy (EIS) Figure 2 As shown in c), all curves are typical Nyquist plots. LMO-Al-F has the lowest charge transfer resistance (Rct = 1.82 Ω), which is lower than that of pure LMO (4.15 Ω), LMO-F (2.53 Ω), and LMO-Al (2.22 Ω), indicating that aluminum-fluorine co-doping accelerates interfacial charge transfer and improves reaction kinetics.
[0074] To verify ion selectivity, the CV response of LMO-Al-F was tested in different single-salt electrolytes. Figure 2 (d) Only LiCl showed a significant high current density redox peak, while NaCl and MgCl2 showed negligible current responses and no clear redox characteristics, indicating minimal competitive ion intercalation / deintercalation. Direct electrochemical analysis confirmed the intrinsic lithium selectivity of LMO-Al-F. This conclusion was verified by constant current charge-discharge with different single-salt electrolytes—only LiCl showed a significant capacity peak, while the responses in NaCl and MgCl2 were negligible.
[0075] CV curves of LMO-Al-F at different scan rates ( Figure 2 As shown in (e), the peak current gradually increases with increasing sweep rate, indicating excellent kinetic performance. Further quantification of the contributions of diffusion control and capacitance control processes ( Figure 2 (f): As the scan rate increases, the capacitance contribution increases and the diffusion contribution decreases, indicating that surface pseudocapacitive behavior dominates at high rates, which is beneficial for rapid lithium capture during RCDI operation.
[0076] The lithium diffusion coefficients of LMO and LMO-Al-F were estimated based on scan rate-dependent CV data. Figure 9 The results showed that LMO-Al-F had a higher diffusion coefficient (Table 2), indicating that it had a lower charge transfer resistance and better lithium intercalation kinetics, which in turn improved the lithium intercalation reaction rate in LMO, resulting in higher lithium adsorption capacity and selectivity.
[0077] Table 2 Comparison of lithium-ion diffusion coefficients between LMO-Al-F and LMO
[0078] application: A series of LMO-based materials were used to fabricate adsorption electrodes and assemble an RCDI system.
[0079] Highly selective electrochemical lithium extraction from actual shale gas wastewater and preparation of electrodes for RCDI testing include the following steps: Adsorption electrodes were fabricated from the materials obtained in Example 1 and Comparative Examples 1-3 and installed in a rocking-chair capacitive deionization (RCDI) device. This device consists of two flow channels, two LMO-based electrodes, and an anion exchange membrane located between the two flow channels. Before formal testing, the assembled RCDI underwent three pre-cycle treatments. Each pre-cycle included a forward constant-current lithiation step and a reverse constant-current delithiation step; in the forward constant-current step, 0.625 A / m was applied. 2 The current density was set for 10 minutes, causing Li + One LMO-based electrode was embedded; then, the same current density was applied in reverse for 10 minutes to delithiate the electrode on one side and lithiate the electrode on the other side. After three cycles of lithiation / delithiation, the electrode response stabilized, and then formal lithium extraction tests were performed.
[0080] The electrochemical lithium recovery process employs a batch recycling model, which is suitable for the actual Li in shale gas wastewater. + Low concentration and Na + Mg 2+ To simulate a complex ionic environment with high concentrations of coexisting ions, a ternary simulated shale gas wastewater was prepared using LiCl, NaCl, and MgCl2. The molar concentrations of LiCl, NaCl, and MgCl2 were 3.0 mM, 300 mM, and 3.0 mM, respectively, with a molar ratio of 1:100:1. 20 mL of the simulated solution was circulated through an RCDI cell at a flow rate of 7 mL / min. During the adsorption phase, an A / m² pressure was applied. 2 A constant current density was applied during the desorption phase, with current densities of the same magnitude but opposite directions. After each adsorption or desorption, rinsing and liquid exchange were performed before starting the next half-cycle. During operation, the LMO-based materials at both electrodes underwent reversible lithiation and delithiation with polarity switching. Anions migrated through the anion exchange membrane to maintain electroneutrality, resulting in lithium-ion enrichment in one channel and lithium-ion depletion in the other. Experimental results are shown below. Figure 3 .
[0081] In a ternary mixture containing LiCl, NaCl, and MgCl2 (molar ratio 1:100:1) (simulating the lithium, sodium, and magnesium concentrations in shale gas produced water), the lithium intercalation selectivity of LMO-based materials and a series of modified materials was tested. For example... Figure 3 As shown, the original LMO material in Comparative Example 3 affects Li + The presence of selectivity indicates that the lithium vacancies formed after delithiation of spinel LMO possess a certain degree of Li... + Recognition capability; Compared with the comparative materials, the Li / Na and Li / Mg selectivity factors of the LMO-Al-F material obtained in Example 1 were significantly improved, indicating that Al / F co-doping can further enhance the material's Li... + The selective intercalation capability demonstrates that the imprinted vacancies generated after delithiation of spinel LMO have a specific recognition ability for lithium and can be targeted for lithium intercalation. This is due to the smaller radius of lithium ions and the lower dehydration energy (Table 3).
[0082] Table 3. Ionic radius, hydration radius, and hydration free energy of metal ions.
[0083] like Figure 3 As shown in Figure a: During operation, the LMO-based materials at both electrodes undergo reversible lithiation / delithiation with polarity switching, and anions migrate through the anion exchange membrane to maintain electroneutrality. After each adsorption / desorption cycle, rinsing and liquid flow exchange are performed before starting the next half-cycle. The LMO-based materials achieve selective lithium insertion through size sieving or the enthalpy effect of hydration, while other ions are effectively repelled. Figure 3The diagram in section b shows that periodic current reversal enables stable cycling of the RCDI battery, with alternating enrichment and depletion of lithium concentration in channels A and B, confirming continuous and controllable separation of lithium ions during charge-discharge cycles. Figure 3 The results show that the selectivity factor of LMO-Al-F is significantly higher than that of other materials. The synergistic effect of aluminum and fluorine makes it more difficult for other coexisting ions to participate in the intercalation reaction, thus achieving higher lithium selectivity. This trend is consistent with the results of the doping ratio screening, where the separation factor reaches its peak at the optimal aluminum / fluorine ratio. Figure 10 ).
[0084] Lithium extraction energy consumption test ( Figure 3 (d) indicates that the energy consumption of LMO-Al-F is low, suggesting that higher lithium adsorption capacity results in lower energy consumption for extracting the same amount of lithium. The lowest energy consumption occurs at the optimal co-doping ratio, not at a higher doping amount. Figure 11 ).
[0085] Besides material composition, operating parameters also affect the lithium extraction behavior of LMO-Al-F. Increasing current density improves lithium adsorption capacity, but increases energy consumption and decreases lithium / sodium and lithium / magnesium separation factors. Figure 12 This indicates that there is an inherent trade-off between extraction rate and separation performance; while excessively high current density is beneficial for lithium capture, it reduces selectivity and energy efficiency.
[0086] Using actual shale gas wastewater (Table 4), the application potential of the LMO-Al-FRCDI system for electrochemical lithium recovery was further evaluated. Figure 3 The results showed that lithium removal rate was extremely high, while removal rates of competing ions such as sodium, potassium, magnesium, and calcium were negligible (even though sodium ion concentrations were higher). Analysis of the recovered liquid showed that lithium concentration was significantly higher than that of other interfering ions. Figure 3 The inset in Figure e compares the separation factors of pure LMO and LMO-Al-F, confirming that aluminum-fluorine co-doping significantly improves the selectivity of lithium relative to all competing ions. The results indicate that the LMO-Al-F electrode maintains strong lithium preference and efficient ion discrimination capability even in complex electrolyte environments, demonstrating excellent selectivity for lithium.
[0087] Table 4. Ion concentrations in actual shale gas production wastewater
[0088] To reveal the root cause of the improved lithium selectivity and structural stability in LMO-Al-F at the microscopic level, in-situ Raman spectroscopy was conducted.
[0089] During electrochemical lithiation / delithiation, the LMO lattice inevitably undergoes reversible structural "breathing." In-situ Raman spectroscopy was used to directly track the local and long-range structural evolution of LMO-Al-F during operation. Results ( Figure 4As shown in a), the characteristic Raman peaks of the spinel framework are well preserved throughout the entire potential window, with only reversible intensity modulation and no obvious peak splitting or irreversible shift. This indicates that the Mn-O octahedral framework undergoes highly reversible distortion during lithium insertion / extraction, effectively suppressing irreversible Ginger-Taylor distortion.
[0090] The LMO-Al-F electrode was subjected to 100 cycles of stability testing in 5 mM LiCl solution at a current density of 20 mA / g. The results are shown below. Figure 14 As shown in the figure, the lithium adsorption capacity retention rate of LMO-Al-F after 100 cycles is not less than 90%, which is better than that of undoped LMO; the manganese dissolution rate is low after cycling, and no obvious structural changes are observed in XRD after cycling. Figure 14 This indicates that aluminum-fluorine co-doping can effectively improve the long-term operational stability of LMO electrodes.
[0091] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. The application of a lithium manganese oxide material in highly selective electrochemical lithium extraction from shale gas wastewater, characterized in that, The lithium manganese oxide material is a spinel-type lithium manganese oxide co-modified with aluminum and fluorine. Aluminum replaces some manganese sites to increase the average valence state of manganese and strengthen the bulk spinel structure, while fluorine replaces some oxygen sites or accumulates on the material surface to form a fluorine-containing passivation layer. This lithium manganese oxide material serves as the active material for a lithium-ion sieve electrode, enabling selective insertion and release of lithium ions in an electrochemical lithium extraction system. The electrochemical lithium extraction employs a rocking-chair capacitor deionization system. Before lithium adsorption, the lithium-ion sieve electrode undergoes pre-delithiation under 0.8V vs. Ag / AgCl conditions to create lithium adsorption vacancies. The lithium manganese oxide material is prepared by the following method: Lithium, manganese and aluminum sources are mixed in a solvent, the solvent is heated to evaporate, and the mixture is dried to obtain precursor powder. The obtained precursor powder was calcined in air for the first time to obtain aluminum-doped lithium manganese oxide. The obtained aluminum-doped lithium manganese oxide was mixed and ground with a fluorine source, and then subjected to a second heating and calcination to obtain lithium manganese oxide material.
2. The application according to claim 1, characterized in that, The molar ratio of Li, Mn, and Al in the lithium source, manganese source, and aluminum source is 1:(1.90-1.99):(0.01-0.10); The lithium source is selected from one or more of lithium hydroxide (LiOH), lithium carbonate (Li2CO3), lithium acetate (CH3COOLi), and lithium nitrate (LiNO3); The manganese source is selected from one or more of manganese acetate Mn(CH3COO)2, manganese nitrate Mn(NO3)2, manganese carbonate MnCO3, and manganese oxide MnO; The aluminum source is selected from one or more of basic aluminum acetate Al(OH)(CH3COO)2·2H2O, aluminum nitrate Al(NO3)3, aluminum acetate Al(CH3COO)3, and aluminum hydroxide Al(OH)3.
3. The application according to claim 1, characterized in that, The first heating and calcination process includes two steps: preheating and calcination. The preheating temperature is 400-600°C and the time is 5-9 hours; the calcination temperature is 700-800°C and the time is 8-12 hours.
4. The application according to claim 1, characterized in that, The fluorine source is selected from one or more of ammonium fluoride (NH4F), lithium fluoride (LiF), ammonium hydrogen fluoride (NH4HF2), and sodium fluoride (NaF).
5. The application according to claim 1, characterized in that, The second heating and calcination temperature is 350~450°C, and the time is 1~4 hours; The mass ratio of aluminum-doped lithium manganese oxide to fluorine source is (50-100):
1.
6. The application according to claim 1, characterized in that, The preparation of the active material of the lithium-ion sieve electrode includes the following steps: mixing lithium manganese oxide material with a binder and a conductive agent, and dispersing it in an organic solvent to form an electrode slurry; coating the electrode slurry on graphite paper and drying it to obtain the lithium-ion sieve electrode.
7. The application according to claim 6, characterized in that, The binder is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, Nafion, and sodium carboxymethyl cellulose; The conductive agent is selected from one or more of conductive carbon black, acetylene black, carbon nanotubes, graphene, and graphite powder. The organic solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and γ-butyrolactone; The mass ratio of the lithium manganese oxide material, binder and conductive agent is (70-90):(5-20):(5-20).
8. The application according to claim 1, characterized in that, Shale gas wastewater contains Li + Na + Mg 2+ K + and Ca 2+ Multiple coexisting ions; The rocking chair type capacitor deionization system includes a lithium manganese oxide electrode, two flow channels, and an anion exchange membrane disposed between the two flow channels. In the rocking chair capacitive deionization system, the flow rate of shale gas wastewater or simulated shale gas wastewater is 3-15 mL / min, and it operates in constant current mode. The applied current density during adsorption is 0.25-0.75 A / m. 2 During the desorption process, the same current density is applied in opposite directions.
Citation Information
Patent Citations
Doping modified lithium ion sieve and preparation method thereof
CN114100562A
